Recent Advances in Organic Room Temperature Phosphorescence of Triphenylamine‐Based Doping Systems. Issue 3 (8th December 2022) - Li, Gengchen; Dai, Wenbo; Lei, Yunxiang; Shi, Jianbing; Tong, Bin; Cai, Zhengxu; Dong, Yuping
Abstract: The host–guest doping strategy has become one of the most effective approaches to realize pure organic room temperature phosphorescence (RTP). Crystalline small molecules can provide a rigid environment that restricts the molecular motion of luminescent guests, thus enhancing phosphorescence emission. Triphenylamine (TPA) is a classic crystalline small molecule matrix that, when doped with designed guest molecules, enables tunable RTP properties and diverse functionalities. These properties afford TPA‐based doping systems with numerous applications in anticounterfeiting, bio‐imaging, and multiple responsive sensing. In this concept, design strategies, luminescence mechanisms, and applications of TPA‐based host‐guest doping systems are summarized. Moreover, the future prospects of TPA‐based RTP materials are proposed. Abstract : A good host : Triphenylamine is commonly used as a host to realize room temperature phosphorescence in host‐guest systems. The good crystallinity, low energy levels, and electron‐rich nature provide excellent photophysical characteristics. This Concept also discusses how these systems have found application in fields such as bioimaging, anti‐counterfeiting, and multi‐stimuli‐responsive emission.